Minimally invasive sinus tarsi approach in Sanders II-III calcaneal fractures in high-demand patients - Paolo Ceccarini; Francesco Manfreda; Rosario Petruccelli; Giuseppe Talesa; Giuseppe Rinonapoli; Auro Caraffa (Medicinski glasnik, 2020)
Aim: To evaluate if the sinus tarsi approach treated with open reduction and internal fixation (ORIF), without using plate fixation, provided good functional results in active adult population. The hypothesis was that the sinus tarsi approach with limited incision provided good results comparable to other approaches. Methods: A total of 78 patients (81 feet) surgically treated for articular calcaneus fracture were reviewed according to inclusion criteria: Sanders fracture type II-III, minimum follow-up of 2 years, patients aged 18-65 years. Exclusion criteria were smokers, diabetics, non-collaborative patients and patients with Sanders fracture type I and IV. A mean follow-up was 52.6 months. Radiographic changes of the Bohler's angle were reported. For the clinical evaluation, Visual Analogue Scale (VAS) for calcaneal fractures, American Orthopaedic Foot and Ankle Society (AOFAS) score and Maryland Foot Score (MFS) were used. Results: A statistically significant restitution of Böhler's angle from preoperative to postoperative (13.5°-27°; p<.001) was found. The AOFAS and MFS showed pain relief and good/excellent functional activities at the final follow-up in 65 of 78 (83.3%) patients. In eight (out of 81; 10%) feet a superficial wound infection was observed. In three (3.8%) patients a subtalar arthrodesis was performed. Conclusion: The mini-invasive sinus tarsi approach for active adult population is a valid and reproducible technique with a low rate of major complications, but it is mandatory advice to patients regarding the expectation of the results.
Keywords: foot and ankle trauma; hindfoot surgery; mini-invasive surgery; outcome scoring